“Those risks, that preventative work, that is the bedrock of family medicine”: A foucauldian discourse analysis of communicating risk for type 2 diabetes among primary care providers - Wendy M. Blunt; Jennifer D. Irwin; Robert J. Petrella; Jacob Shelley; Maxwell J. Smith (BMC Primary Care)
Abstract With estimates suggesting 350 million individuals are at-risk for type 2 diabetes (T2D), there is an urgent need to critically understand the processes of risk communication with primary care providers. Prior research has shown that primary care is the most likely place where initial conversations with a patients about T2D risk occur, but there remains a paucity of research exploring what may govern this communication. The purpose of this study was to critically explore discourses of risk for preventing T2D from the perspective of primary care providers. Semi-structured interviews (n = 14) were conducted with primary care providers including family physicians (n = 4), medical residents (n = 2), nurses (n = 3), dietitians (n = 4), and a pharmacist (n = 1) working in family health team (FHT) clinics in Southwestern, Ontario, Canada. Foucauldian Discourse Analysis through thematic analysis was applied to analyze the data and generate themes detailing how provider communications about risk for T2D are governed through discourse. Themes included: (1) patient-centred practice; (2) diagnosing prediabetes; (3) contextualizing symptoms; (4) time contingent; (5) adapting to patient knowledge; (6) carefully discussing weight; and (7) age as a balancing act. Overall, providers note using discourses of patient-centred practice to guide approaches to communicating about risk for T2D to patients. There are tensions with fulfilling this ideal patient-centred approach from more powerful discourses of prediabetes, assumptions about patient knowledge, and age that may override the ability to be patient-centred with communications about risk for T2D.